Segmentation versus integration in visual motion processing. - Braddick, O (1993)
Reliable motion perception requires processes that integrate visual motion signals from neighbouring locations in the visual field, which should have the effect of smoothing out spatial variations in velocity. However, we also require motion processing to be very sensitive to local velocity differences, so that moving objects appear sharply distinct from their background and specific differential properties of optic flow associated with the observer's motion can be detected. Perceptual experiments give evidence both for integrative processes, which lead to spreading of perceived motion, and for differential processes, which lead to motion contrast and segmentation. Current and future experiments might allow tests of theoretical schemes that employ adaptive networks and/or multiple representations in order to reconcile the conflicting demands of integration and segmentation.